Hiawatha's Childhood - Henry Longfellow (Symphony in the Flint Hills, 2019)
Introduction: Saw the fire-fly Wah-wah-taysee, Flitting through the dusk of evening, With the twinkle of its candle Lighting up the brakes and bushes. (Excerpted from: Hiawatha's Childhood, Henry Wadsworth Longfellow, 1893.)